Building Teacher Personal Identity: An Autobiography of an Indonesian Non-native English Teacher - Makhsun, Faizal Ali; Fauziati, Endang; Sumardi, Sumardi (VELES Voices of English Language Education Society, 2023)
This research explores the professional identity formation of non-native English-speaking teachers (NNESTs) from a personal viewpoint, an area not extensively covered in existing literature. While there is a wealth of discussion on teacher professional identity, the subjective experiences of NNESTs in shaping their own identities are often overlooked. This autobiographical narrative study addresses this gap by examining my own experiences as an NNEST, integrating reflections from my time as a student and my practice as a teacher. Employing thematic analysis, this research scrutinizes reflection data and artifacts gathered throughout my academic and professional journey. This method allows for a comprehensive examination of how various experiences influence professional identity formation. The findings reveal that an NNEST's professional identity is significantly shaped by the professional context, which includes direct teaching experiences and teacher education, as well as the external political environment, such as government policies and efforts to improve educational quality. The study is particularly relevant in the context of developing countries, like Indonesia, highlighting the intricate relationship between personal experiences, professional settings, and the wider political context in the development of NNEST identities. This research contributes a unique perspective to the field of teacher identity and underscores the distinct challenges and influences that NNESTs encounter in their professional growth.